Sowing Q methodology in the rural global South: a review of challenges and good practices - Juan Carlo Intriago Zambrano; Jan Carel Diehl; Maurits W. Ertsen (Cogent Social Sciences, 2024)
The accomplishment of Sustainable Development Goals (SDGs) is intrinsically connected to improving livelihoods in the Rural Global South (RGS). RGS livelihoods are complex, showing multiple dimensions beyond mere economic considerations. However, many related development policies (over)simplify livelihoods to income thresholds, leading to flawed interventions. Adequate strategies to address RGS livelihoods require a much deeper understanding of their various dimensions and complexities. Q methodology (Q) is a powerful participatory research technique that enables the systematic study of different viewpoints on subjective topics. Moreover, it has the potential to identify and reveal previously unheard narratives, thus allowing us to question the traditional understandings of RGS livelihoods. Yet, as a time- and assistance-intensive technique, its implementation faces methodological challenges that are currently overlooked and ought to be considered. We selected and reviewed 50 Q studies applied to different forms of RGS livelihoods. First, we discuss several on-field Q limitations associated with the physical, logistical, social, and cultural constraints. Second, we draw on good practices and strategies to cope with these limitations. Notwithstanding the limitations and strategies, we advocate building Q capacities and the gender-balanced empowerment of local researchers. This may contribute to a better understanding of the nuances and challenges of RGS livelihoods.